Variation in health-care quality and outcomes according to time of chest pain presentation: a state-wide prospective cohort study. (3rd October 2022) - Navani, R V; Dawson, L; Andrew, E; Nehme, Z; Bloom, J; Cox, S; Anderson, D; Stephenson, M; Lefkovits, J; Taylor, A; Kaye, D; Smith, K; et al.
Abstract: Background: Previous studies examining temporal variation in cardiovascular care have largely been limited to assessing weekend and after-hours effects whereby those presenting on the weekend or after-hours have a poorer outcome. However, emerging evidence suggests more complex patterns in patterns and outcomes may exist. Purpose: We aimed to determine patterns of temporal variation in chest pain presentations and subsequent health-care quality and outcomes. Methods: This was an observational, prospective-cohort study of adult patients aged 18 and over who were attended by emergency medical services for non-traumatic chest pain between 1 January 2015 and 30 June 2019 in Victoria, Australia. Major exclusion criteria included pre-hospital diagnosis of ST elevation myocardial infarction or an out of hospital cardiac arrest. The exposure variable was time of day and day of week stratified into 168 hourly time periods. The primary outcome measure was 30-day mortality. Results: The study cohort comprised 196, 365 ambulance attendances for acute non-traumatic chest pain; mean age 62.4 years (SD 18.3) and 99, 497 (50.7%) females. Three temporal patterns were observed for chest pain presentations (Figure 1): (1) a diurnal pattern with a sharp increase in presentations from 8 am, peaking around midday, before decreasing into late evening with a nadir between 3–4 am, (2) a weekend effect where Saturday and Sunday had a relatively lower rate of presentations compared to during the week, and (3) a Monday – Sunday gradient where more presentations were likely earlier in the week, than later. Six patterns were identified across pre-hospital and hospital key performance indicators (KPI) (diurnal, in/after-hours, weekend effect, Monday – Sunday gradient, a peak period and morning vs afternoon/evening effect. Risk of 30-day mortality was associated with weekend presentation (OR 1.15, 95% CI 1.06–1.24, p=0.001) and morning presentation between midnight and midday (OR 1.17, 95% CI 1.09–1.25, p<0.001) (Figure 2). Conclusion: Chest pain presentations, care quality and outcomes demonstrate complex temporal variation beyond the already established weekend and after-hours effect. Such relationships should be considered during resource allocation and quality improvement programs in order to improve treatment quality across all days and times of the week. Funding Acknowledgement: Type of funding sources: None.